Monte Carlo modeling for electron microscopy and microanalysis - Joy, David C., 1943- (Oxford series in optical and imaging sciences ;, 1995)
1. Preface. 2. An Introduction to Monte Carlo Methods. 3. Constructing a Simulation. 4. The Single Scattering Model. 5. The Plural Scattering Model. 6. Practical Applications of Monte Carlo Models. 7. Backscattered Electrons. 8. Charge Collection and Cathodoluminescence. 9. Secondary Electrons and Imaging. 10. X-Ray Production and Micro-Analysis. 11. What Next in Monte Carlo Simulations?